Target molecules for future hidradenitis suppurativa treatment. (4th June 2021) - Zouboulis, Christos C.; Frew, John W.; Giamarellos‐Bourboulis, Evangelos J.; Jemec, Gregor B.E.; del Marmol, Veronique; Marzano, Angelo V.; Nikolakis, Georgios; Sayed, Christopher J.; Tzellos, Thrasyvoulos; Wolk, Kerstin; Prens, Errol P.
Abstract: The registration of the tumour necrosis factor‐α inhibitor adalimumab in 2015 was a major step forward in the treatment of hidradenitis suppurativa/acne inversa (HS). However, it soon became evident that the effectiveness of adalimumab in daily practice was highly variable. A significant unmet medical need of HS patients remained, and the search for novel therapeutic targets was intensified. During the 10th European Hidradenitis Suppurativa Foundation (EHSF) e.V. Conference, reknown international HS investigators virtually presented and discussed the published data on these potential target molecules for future HS treatment. This article addresses the most promising molecules currently under investigation from a pathophysiological and clinical point of view. With phase III trials ongoing, the anti‐ interleukin (IL)‐17 biologics bimekizumab and secukinumab are in the most advanced stage of clinical development showing promising results. In addition, targeting IL‐1α with bermekimab has shown encouraging results in two clinical trials. Directing treatment at neutrophil recruitment and activation by targeting IL‐36 with spesolimab fits well in the pathogenic concept of HS and clinical phase II trial results are pending. In contrast to in situ evidence, Complement 5a (C5a) and C5a receptor blockade have only shown greater clinical benefit in patients with severe HS. Inhibition of Janus kinase (JAK) 1 signalling in HS showed clinical efficacy only in the highest dosage, highlighting that careful surveillance of the balance between safety and efficacy of JAK inhibition is warranted. Overall, clinical efficacies of all novel treatments reported so far are modest. To guide drug development, more and better‐defined translational data on the pathogenesis of this severe and enigmatic inflammatory skin disease are required.